Assessment of knowledge and decision-making regarding dental trauma among primary school teachers in south Bangalore- a cross-sectional survey - Nongmeikapam, Rejita; Kumar, Manish; Surbala Devi, Rajkumari; Murthy, Mamatha; S. G., Sushma; Nongmeikapam, Dhimi (International Journal Of Community Medicine And Public Health, 2023)
Background: Injury to primary and permanent dentitions is one of the most common dental problems seen in school going children. Teachers play an important role in prevention of dental trauma and immediate management of the injured tooth. Hence, the aimed of the study was to evaluate primary school teachers’ knowledge and decision making regarding dental trauma in South Bangalore, Karnataka. Methods: A cross-sectional survey was conducted among 400 primary school teachers in South Bangalore, using self-administered pretested questionnaire consisting 16 close-ended questions. Results: Among 400 primary school teachers, 212 participants could identify the damaged front teeth likely to be permanent teeth. Almost half of the participants would seek the dentists help immediately and only 74 respondents would not mind the delay of 30 minutes. Most of the respondents would clean the dirty tooth in tap water and only 16 respondents would use milk for transporting the avulsed tooth. A great majority of the respondents were satisfied with the knowledge on the management of dental trauma but most of them expressed desire for further knowledge. Conclusions: The research clearly revealed that majority of school teachers had very less knowledge related to handling of traumatic dental injuries. First aid training program with dental content and acquisition of dental injury management should be included in the curriculum of teachers training program.